Pengaruh Keputusan Investasi, Kebijakan Deviden,Kebijakan Hutang Dan Profitabilitas Terhadap NilaiPerusahaan(Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di BEITahun 2010-2013) - Noviana, Riska; , Dr. Erma Setiawati, AK., MM (2016)
The purpose of this research is to examine the significant impact of Investment Decision, Devidend Policy,Debt Policy and Profitability in Price Book Value at manufacturing companies listed in Bursa Efek Indonesia during 2010- 2013. The method of this research is purposive sampling with 31 companies as a sample for every year. This research is done for 2010-2013 period. This research utilizies secondary data. The data are taken from the website Bursa Efek Indonesia (www.idx.co.id). The data which is analyzed in this research are collected through Indonesian Capital Market Directory (ICMD) and Annual Report. The data which have already collected are processed with classic assumption test before hypothesis test. Hypothesis test in this research use double regression with t test, F test and coefficient determination test. The result of this research show that partially Investment Decision and Profitability have a significant impact to Price Book Value. Whereas, Devidend Policy and Debt Policy don't have a significant impact to Price Book Value. Investment Decision, Devidend Policy, Debt Policy and Profitability have a significant impact to Price Book Value simultaneously.